Pendampingan Pengelolaan Keuangan Sekolah Melalui Peningkatan Pemahaman Literasi Keuangan Syariah - Makhrus Makhrus; Safitri Mukarromah; Makhful Makhful (UM Purwokerto Press, 2022)
The development of Islamic financial institutions in Indonesia over the last three decades has shown encouraging developments, this is indicated by the increasing number of sharia-based financial institutions. The purpose of the community service activities that have been carried out is to provide comprehensive understanding and insight about the importance of Islamic financial literacy, provide motivational encouragement, and an understanding of the importance of managing school finances that can be managed using sharia principles.The method used in this activity is the holding of Islamic financial literacy socialization which is directed at school financial management by providing material on contract theory, sharia business contracts, and Islamic financial institutions. Meanwhile, the participants in this activity were delegated teachers from Muhammadiyah schools in Banyumas Regency. The results of this activity show that school financial management is carried out differently according to school policies. The form of the policy is adjusted to the cooperation of schools with financial institutions, both BTM, BMT and commercial banks (Islamic banks and conventional banks). The delivery of material in this activity uses a participatory-dialogical method, where participants can convey their ideas and views, while the presenters only become facilitators by providing a review of participant responses. The form of practice in which the participants were directed by the implementing team was to get to know the various sharia contracts, while the participants' responses to the implementation process were mostly very good and good, and hoped that they would be implemented continuously.